Effective bank corporate governance: Observations from the market crash and recommendations for policy - Moorad Choudhry (Journal of Applied Finance & Banking, 2011)
This paper considers the extent to which inadequate corporate governance was a contributory factor to the financial market crash. It examines the experience of selected failed banks, with emphasis on the corporate governance structure in place at each firm, and the background and expertise of the Board and Directors, and draws conclusions for future policy. We find that the nature and composition of Boards was not robust enough to provide independent direction. Their membership possessed insufficient expertise, and was not geared towards a long-term view of the bank's development. Consequently many banks were drawn into a bull market spiral. The form of management direction contributed to this. Based on our conclusions we recommend that a number of bank governance measures be implemented, if necessary for imposition by regulatory fiat. These measures relate to the composition, structure and expertise of board members and non-executive directors.
Keywords: H12; G32; G28; 330; corporate governance; financial institutions; board strategy; regulatory policy; management infrastructure